ADAKAH KONSEP FINIT DALAM BAHASA SUNDA? - Kurniawan, Eri (Linguistik Indonesia, 2013)
This paper presents an argument that there are no overt morphological manifestations of finiteness in Sundanese. It also provides pieces of evidence that temporal/aspectual auxiliaries do not determine finiteness, as opposed to Kana’s (1986) and Arka’s (2000, 2011) claim for Indonesian. Nor are person agreement and modality shown to correlate with a finiteness opposition. Nevertheless, this paper argues that finiteness seems to be at work in Sundanese and that it patterns like other languages to account for the distribution of overt subjects. More specifically, it is proposed that it is the presence of an abstract [finite] feature that licenses an overt subject in a finite clause. As an implication, this establishes a clear-cut dividing line in terms of finiteness along which clausal complements are differentiated. An indicative complement clause is finite owing to their ability of licensing an overt subject, whereas raising and control complements are all non-finite due to the inadmissibility of an overt subject.